Special products using non traditional raw material - Ivanova, Tatiana; Peshuk, Ludmila (My University, 2015)
Traditionally, in our country, meat products are made from beef, pork and poultry. However, from the point of view of the science of food, these types of raw meat is largely inferior to the meat of wild animals, which has always been a healthy and nutritious food, as wild animals eat only natural forage. Moreover, they live far away from industrial areas, have active mode of life, which positively affects the consistency of meat, it is quite dense and contains of a small amount of fat.
Keywords: alternative raw; animal feed; meat products; нетрадиційна сировина; корм для тварин; м'ясні вироби; нетрадиционная сырье; корм для животных; мясные изделия; кафедра технології м’яса і м’ясних продуктів